Efficacite du Top Bio et de L’huile de Thevetia Contre les Chenilles Carpophages du Cotonnier au Centre du Benin - AZONKPIN, Saturnin; DJIHINTO, Cocou Angelo; CHOUGOUROU, CHÈPO DANIEL (My University, 2020)
Botanical pesticides used in the control of insect pests of crops are nowadays an alternative to synthetic pesticides. This study evaluated the effectiveness of Top bio and Thevetia oil in the fight against cotton carpophagous pests. The experimental design was a Fisher Blocks with 6 treatments replicated 4 times. The six treatments were: the control or Untreated, agri-bio-pesticide dosed at 1 l / ha, two doses of Top bio (2 l / ha and 3 l / ha) and two doses of Thevetia oil (1% and 2%). Linear models and generalized linear with fixed and mixed effects were used to test the influence of treatments on Carpophagous caterpillars and their damage at Gobé. The number of caterpillars of Helicoverpa armigera varied from 0.15 (top bio 3 l / ha and Thevetia oil 2%) to 1.5 (Untreated) in 2015. The number of caterpillars of Earias biplaga fluctuated between 2.81 (Thevetia oil 2%) and 5.84 (Untreated) in 2016. The number of caterpillars of Pectinophora gossypiella varied from 0.75 (agri-bio-pesticide) to 3.45 (Untreated) in 2015. The number of Thaumatotibia leucotreta caterpillars fluctuated between 2.28 (Top bio 2 l / ha) and 8.00 for control treatment in 2016. The percentage of healthy green capsules varied from 14.25 ± 2.8% (Untreated) to 26.25 ± 2.8 % (Thevetia oil). The percentage of ripe, tracked capsules varied from 39.85 ± 8.90% for Top bio at 2 l / ha) to 64.96 ± 4.90% for control treatment. The compared biopesticides were effective against H. armigera, E. biplaga, P. gossypiella at their low dose. But the 1% dose of Thevetia oil was ineffective on T. leucotreta which was controlled by the 2% dose. These biopesticides can be used as an alternative in the fight against carpophagous caterpillars in organic cotton cultivation.
Keywords: Biopesticides; pests; damage; organic cotton; Benin.